Hcv infection and treatment rates in opioid dependent patients hospitalized in an alcohol and drug addiction treatment center clinic - Toker Uğurlu, Tuğçe; Güvendik, Cansu; Ateşci, Figen (Journal of Dependence, 2020)
Objective: The aim of this study was to investigate the factors related with anti HCV positivity rates and post discharge hepatitis C infection follow-up and treatment rates of the patients who was diagnosed with opioid use disorder. Method: The data of this study was collected by retrospective examination of the records of 265 patients aged 18 and over who were diagnosed with opioid use disorder according to DSM-5 diagnostic criteria and received inpatient treatment in an Alcohol and Drug Addiction Treatment Center (ADATC) clinic between 2017 and 2018. Results: Anti HCV was positive in all male gender and 10.9% (n=29) patients. It was found that 6.9% (n=2) of the anti HCV positive patients continued their regular outpatient controls after discharge, while anti HCV negative patients came to regular controls at a statistically significant rate with 25.1% (n=59). As a result of the orientation after discharge, 31% of anti HCV positive patients applied to the department of infectious diseases, and 44.4% (n=4) of applicants received direct antiviral therapy. Conclusion: Treatment compliance of the patients with anti HCV positivity was insufficient in terms of both opioid use and hepatitis C infection. New strategies should be developed to struggle HCV infection in addicted patients in order to direct the patients to treatment, to stay in treatment and to ensure their regular follow-up.